2005
DOI: 10.1002/syn.20220
|View full text |Cite
|
Sign up to set email alerts
|

Repeated antipsychotic drug exposurein developing rats: Dopamine receptor effects

Abstract: Antipsychotic drugs are often prescribed to juvenile psychiatric patients, though their cerebral effects during development are incompletely described. Accordingly, we studied the effects of repeated treatment with dissimilar antipsychotic drugs on dopamine (DA) receptors in juvenile vs. adult rats. Tissue levels of DA receptor types (D1, D2, D3, and D4) in forebrain regions of juvenile rats were quantified after 3 weeks of daily treatment with representative first- (fluphenazine) and second-generation (clozap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
43
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(49 citation statements)
references
References 50 publications
6
43
0
Order By: Relevance
“…For instance, Moran-Gates et al (2006) found that repeated administration of OLZ (5 mg/kg, once daily) and CLZ (20 mg/kg, twice daily) from P 22 to P 42, all decreased D 1 receptors in dorsolateral frontal and medial prefrontal cortex of adolescent, but not adult rats. In contrast, both drugs increased D 2 receptors in the medial prefrontal cortex of adult, but not adolescent rats (Moran-Gates et al, 2006). OLZ, but not CLZ, also increased D 2 receptor levels in hippocampus, and D 4 levels in nucleus accumbens and caudate-putamen in both juvenile and adult rats.…”
Section: Discussionmentioning
confidence: 75%
See 2 more Smart Citations
“…For instance, Moran-Gates et al (2006) found that repeated administration of OLZ (5 mg/kg, once daily) and CLZ (20 mg/kg, twice daily) from P 22 to P 42, all decreased D 1 receptors in dorsolateral frontal and medial prefrontal cortex of adolescent, but not adult rats. In contrast, both drugs increased D 2 receptors in the medial prefrontal cortex of adult, but not adolescent rats (Moran-Gates et al, 2006). OLZ, but not CLZ, also increased D 2 receptor levels in hippocampus, and D 4 levels in nucleus accumbens and caudate-putamen in both juvenile and adult rats.…”
Section: Discussionmentioning
confidence: 75%
“…One is the age difference in psychopharmacological responsiveness and brain responses to antipsychotics between adolescent animals and adult ones (Spear and Brake, 1983;Moran-Gates et al, 2006;Wiley, 2008;Choi et al, 2010). The common approach is to compare animals in different age groups on their behavioral responses (eg, locomotor activity, catalepsy; Wiley and Evans, 2008) and brain responses (eg, dopamine and 5-HT receptors; Moran-Gates et al, 2006;Choi et al, 2010) to various antipsychotic treatments, without tracking changes across the different development stages. The second issue of interest is the long-term behavioral and brain consequences of antipsychotic treatment in adolescence (Llorente-Berzal et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarities of findings on dopamine receptors (a reduced D1 binding in MPC and increased D2 binding in NAc) at both proximal to (Moran-Gates et al 2006) and long after chronic adolescent exposure as in the above two studies suggest that these changes may indeed persist from adolescence to adulthood. Moreover, chronic olanzapine treatment in adolescence has also been reported to induce a long-lasting reduction in levels of glutamate and GABA in the NAc (Xu et al 2015).…”
Section: Neurochemical Outcomes That Persist Long After Adolescent Apsupporting
confidence: 79%
“…binding in the NAc induced by olanzapine treatment appear to persist from adolescence to adulthood given reports of these changes both proximal to (Moran-Gates et al 2006) and long after chronic exposure . Chronic adolescent olanzapine administration could also induce long-lasting changes in the NAc such as reduced D1 receptor binding, increased D2 receptor binding, decreased evoked DA release ) and reduced levels of glutamate and GABA (Xu et al 2015).…”
Section: Apdsmentioning
confidence: 99%